Filling parameters and process optimization of mining–filling synergistic coal-based solid waste paste in Renjiazhuang mine - Li, Chao; Chen, Denghong; Yang, Ke (Frontiers in Materials, 2023)
This paper focuses on the engineering background of the 110904 filling working face of Renjiazhuang Mine. The limit caving step and periodic weighting step of the working face are analyzed through theoretical analysis, numerical simulation, and field practice. The mining-filling coordination scheme of 'three mining and one filling' is determined. The numerical simulation confirms that the scheme can ensure the spatial and temporal continuity of the mining and filling cycle during the production process, thus demonstrating its theoretical feasibility. Nine sets of orthogonal simulation tests were conducted to investigate the impact of filling ratio and 1d strength of filling materials on the filling effect. By performing extremum difference analysis, it was determined that the filling ratio is the primary factor influencing the filling effect. Moreover, the filling ratio and 1d strength were found to have a positive correlation with the filling effect. The pipehanging filling is carried out in the return airway of the 110904 working face. The ' three mining and one filling ' combined with the 1d strength of the filling material is 2 MPa, and the filling ratio is 80%. The synergistic scheme of mining and filling achieves the expected effect, which is feasible.The plugging problem in the filling process needs to be further optimized in the subsequent filling material ratio scheme. The mining-filling synergistic process proposed in this paper can provide a theoretical reference for the same type of filling working face.